BILLY SHEEHAN’S BASS PLAYING TECHNIQUE IN THE SONG OBLIVION - Ravi Arjuna Sundari; Perry Rumengan; Franklin Dumais (SoCul: International Journal of Research in Social Cultural Issues, 2022)
The bass player played a significant role in something of a band's team, though in a rock band more than a guitar player or vocalist. Billy Sheehan is a different figure in regard to methods, presentation, and progressive acumen in his bass game. Together with The Winery Dongs, they drafted a drill song called Oblivion that combined progressive techniques in their game. The research takes a qualitative approach that reflects the condition of the research object the Oblivion of the bass play method and Billy Sheehan’s key analyzed source information, which the research described in a descriptive way to respond to the research case. Gathering information in the research employs method of documentary study. Based on the findings of this research, Billy Sheehan in a Oblivion song uses a mixture of plucking techniques and tapping techniques combined with the method of lead guitar play. As a result of this study, the authors found that Billy created new styles that made his bass game a unique performance, and looking back on it was a rich bass-game technique.